COĞRAFYA DERSİNDE DRAMA TEKNİĞİNİN ÖĞRENCİ BAŞARISINA ETKİSİ - (:unkn) unknown (My University, 2006)
Bu çalışmada, coğrafya öğretiminde problem çözme yöntemi olarak dramatizasyonun kullanılması ve öğrencinin akademik başarısı ve hatırlama düzeyine etkisi araştırılmıştır. Öğrencilerin cinsiyetinin, ailelerin sosyo-ekonomik durumu, öğrencilerin coğrafya dersine ilgi duyma durumları ve coğrafya dersi ile ilgili değerlendirmelerinin başarıya etkisi, öğrencilerin ders çalışma alışkanlıkları ve ders çalışma ortamlarının başarıya etkileri incelenmiştir.

In this study, the implementation of dramatization as problem solving in geography teaching on the success and recalling level of the students. The effect of the usage of the dramatization method as problem solving strategy in geography teaching on the success and recalling level of the students, the effect of sexes of the students on their success, the affect of the socio-economic situation and education level of the families on students' success, the motivation of the students toward geography course and the effect of the evaluations regarding geography on success level , studying habits of the student and the impact of the studying medium is examined in this study.
The Implementation Of The Drama Technique As Teaching Method In Geography Lessons
Keywords: Eğitim, Eğitim Araştırmaları